GAYA KEPEMIMPINAN KEPALA SEKOLAH MANAGERIAL GRID DALAM MENINGKATKAN KINERJA GURU DI SMPIT UTSMAN BIN AFFAN SURABAYA - Irma Mei Sekarsari; Dhea Syafa Amelia Suwandi; Zahro’ Syarifah Salsabila; Aira Caesarani; Erny Roesminingsih (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the principal’s leadership style based on the Managerial Grid approach in improving teacher performance at SMPIT Utsman bin Affan Surabaya. The study employed a descriptive qualitative method involving the principal, teachers, and students as research subjects. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis used the interactive model of Miles, Huberman, and Saldana, consisting of data condensation, data display, and conclusion drawing. The findings revealed that the principal implemented a leadership style that tended toward Team Management (9,9), characterized by high concern for both task achievement and interpersonal relationships. The principal actively conducted supervision, performance evaluation, and teacher development through training programs and competency improvement activities. In addition, the principal fostered open communication, a family-oriented work culture, and reward systems for high-performing teachers. The implementation of the teacher tahfidz program also served as a means of strengthening discipline and enhancing teacher professionalism. This leadership style positively impacted teacher performance, particularly in discipline, classroom management, work motivation, and professional competency development. A conducive work environment and harmonious relationships further supported.